THE IMPLEMENTATION OF GIST (GENERATING INTERACTION BETWEEN SCHEMATA AND TEXT) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION OF THE TENTH GRADE STUDENTS AT SMAN 16 MAKASSAR - Eman Wahyudi Kasim, Nirmaulana (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2022)
Abstract The objective of the research was to find out whether the implementation of GIST strategy can improve reading comprehension of the tenth grade students of SMAN 16 Makassar. The researcher applied Pre-Experimental method where one group of students was involved .The sample consisted of 40 students who were taken from the tenth grade (X MIA 4 Class) students of SMAN 16 Makassar using purposive sampling technique. The instrument of this research was reading comprehension test which consist of 20 multiple choice items. The data were collected in pretest and posttest and analyzed using SPSS. The result of data analysis showed that the mean score of pretest was 42.00 and posttest was 78.62. It indicates that there was improvement between those mean score. The standard deviation in pretest 14.268 and the posttest was 10.377. In addition, the t-test value of posttest was 0.00 which was smaller than (α) = 0.05. Therefore it concluded that the Implementation of GIST strategy improves the reading comprehension of the tenth grade students at SMAN 16 Makassar. Key terms: Reading Comprehension, GIST (Generating Interaction Between Schemata and Text). Abstrak Tujuan dari penelitian ini adalah untuk mengetahui apakah penerapan strategi GIST dapat meningkatkan pemahaman membaca siswa kelas sepuluh SMAN 16 Makassar. Peneliti menerapkan metode Pra-Eksperimental di mana satu kelompok siswa terlibat. Sampel terdiri dari 40 siswa yang diambil dari siswa kelas X (Kelas X MIA 4) SMAN 16 Makassar dengan menggunakan teknik purposive sampling. Instrumen penelitian ini adalah tes membaca pemahaman yang terdiri dari 20 item pilihan ganda. Data dikumpulkan dalam pretest dan posttest dan dianalisis menggunakan SPSS. Hasil analisis data menunjukkan bahwa skor rata-rata pretest adalah 42,00 dan posttest adalah 78,62. Ini menunjukkan bahwa ada peningkatan antara skor rata-rata tersebut. Simpangan baku pada pretest 14.268 dan posttest adalah 10.377. Selain itu, nilai uji-t postes adalah 0,00 yang lebih kecil dari (α) = 0,05. Oleh karena itu disimpulkan bahwa Implementasi strategi GIST meningkatkan pemahaman membaca siswa kelas sepuluh di SMAN 16 Makassar. Kata kunci: Pemahaman Membaca, GIST